Trend in Age and Racial Disparities in the Receipt of Postlumpectomy Radiation Therapy for Stage I Breast Cancer: 2004-2009. (December 2016) - Yeboa, Debra N.; Xu, Xiao; Jones, Beth A.; Soulos, Pamela; Gross, Cary; Yu, James B.
Abstract : Objectives: Significant effort has been expended over the past decade to reduce racial disparities in breast cancer care. Whether disparities in receipt of appropriate radiotherapy care for breast cancer persisted despite these efforts is unknown, as is the impact of being eligible for Medicare. We therefore investigated trends in racial differences by age in postbreast lumpectomy radiation therapy (PLRT) from 2004 to 2009. Materials and Methods: We analyzed the Surveillance, Epidemiology and End Results registry database for women aged 40 to 85 years who underwent lumpectomy for stage I breast cancer and were eligible for PLRT. We examined variables potentially associated with the receipt of PLRT, including year of diagnosis, race, and examined women separately by age group. Results: Among 67, 124 women aged 40 to 85 years undergoing lumpectomy, receipt of PLRT decreased from 80.7% in 2004 to 76.8% by 2009 ( P <0.001). There remained a persistent disparity in PLRT among African American women (in 2004, 80.6% white vs. 78.9% African American and in 2009, 77.5% white vs. 72.0% African American). In multivariable logistic regression, African American race (odds ratio [OR], 0.82; 95% confidence interval [CI]. 0.76-0.89) and being diagnosed more recently were associated with lower odds of PLRT (OR for 2009 vs. 2004: 0.74; 95% CI, 0.69-0.79), whereas older women typically covered by public health insurance (aged 65 to 69 y) were more likely to receive PLRT (OR, 1.09; 95% CI, 1.02-1.15). Conclusions: PLRT decreased by a significant percentage of 3.9% among all women in recent years, and racial disparities in PLRT receipt have persisted. Medicare eligibility increased the likelihood of PLRT receipt. Abstract : Supplemental Digital Content is available in the text.